Var Sønderjylland i middelalderen en del af Danmarks rige? - Albrectsen, Esben (Historisk Tidsskrift, 1988)
<p id="DIVL508" class="text" style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The present study examines a double question: how was the term Danish Realm understood in the Middle Ages? And what were the contemporary views on the proper legal relationship of Schleswig to the Danish Realm? With regard to the first question, the study shows that, except for the earliest period, contemporaries meant Kingdom when they used the terms Realm, the Danish Realm and also, gradually, Denmark. Correspondingly, the southern boarder of the Danish Realm was identical with the shifting boundary of the Kingdom, and during those times when an independent duchy existed, it was seen as lying outside the Realm. Its ties with the Realm were purely feudal, not territorial. There are no examples from the Fourteenth and Fifteenth Centuries where the terms Realm or Denmark are used as a general designation comprising both the Kingdom and the Duchy. This is directly at odds with the position of the Danish historian Knud Fabricius, who contended that the Danish Realm encompassed the royal fiefs, including Schleswig. <p id="DIVL510" class="text" style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Regarding the second question, the study examines, over a period of two centuries, the views involved in the legal foundations of the struggle over whether Schleswig was properly part of the Kingdom or a more or less autonomous duchy, be it under the dukes of Abel's lineage or the counts of the House of Schauenburg. In the early Middle Ages Schleswig was simply considered as a province within the Realm. As late as 1266 royal domination was still strong enough to sustain the claim that the Duchy was part of the Realm. But afterwards its status as a separate territory prevailed, and powerful Danish kings failed in their attempt to reverse the development in the decades around 1400. From the viewpoint of the Danish monarchy, the best alternative was to tie the territorially separate Duchy to the Realm by clearly defined feudal obligations, and this was the policy that prevailed until 1326, when it was interrupted. But in 1386 Queen Margrethe succeeded in reestablishing the duchy's vassalage and codifying its feudal duties. The local lords of Schleswig for their part, were less consistent in their conceptions of what constituted the most advantageous relationship to the Danish Realm. Twice in the course of the Fourteenth Century they opted for total independence of Denmark, i.e., a repudiation of vassalage and a position of complete autonomy for themselves. Gradually, however, they came to prefer the status of fiefdom, as long as it involved only insignificant obligations to the Danish Crown and Realm. And this was the relationship to which the Oldenburg Kings of Denmark fell heir, when the first of them, in 1460, became the Duke of Schleswig.